Influence of Website Characteristics to Customer Satisfaction on Online Stores - Triesti Candrawati; Retno Widiastuti; Widi Dwi Ernawati (International Journal of Supply Chain Management, 2019)
The development of online business is very rapidly in now days.Therefore, the online business requires a lot of effort compete with similiar business.To be surviving inthe online business can be done by providing maximum satisfaction to consumers and maintaining belief in the products offered both in terms of price and quality of goods by using a good website.The characteristics of the website will be a major concern fot the consumers when they are shopping online, the characteristics website consist of : the convenience of shopping, the site design, informative information, security and communication.The purpose of this study is to determine the effect of Website Characteristicsto Consumers Satisfaction.The research methode in case study at Accounting Management Study Program at Polytechnic State of Malang.The data collected using purposive sampling and Slovin formula.The hypothesis of this research is tested by multiple linier regression.The research results showed that the variable site design, informative, security and communication have a partialy significant effect to the online shopping customer satisfaction, while the convenience of shopping variable is not significant.This understandable because each online store has different system and procedure that incovenience for consumers.